Formal description of electron avalanche in the channel of microchannel plate - Tchoudovskaja, Elena A. (Journal of the Belarusian State University. Physics, 2017)
This article is the formalization description of the secondary emission electron avalanche creation and moving in the channel of the microchannel plate. The position of that channel is perpendicular to the input surface of the plate. There was added the secondary emission coefficient of the semiconductive coverage of the channel to the equation which was received early. This parameter has allowed connecting the output characteristic of the channel with initial parameters of the semiconductive layer. Then, there are the descriptions of the mathematical equations, which have received to describe every electron moving in the avalanche as well inside as outside of the channel. All of those formulas construct the resulting equation, or the analytical model, of the output signal of the MCP. The solution of this equation at the different input data allowed taking into account practically all inside characteristics of the semiconductive emitter and investigating their influence on the output current coefficient. As a result there are offered the calculated graphics of the output gain coefficient in dependence of the layer depth and the gain parameter. There are the calculation results for the distributed cover emitter depth. All the results do not contradict to the experimental data.
Keywords: channel of a microchannel plate; functional equation; the electron transit probability density; equation of motion of particles in the electric field; emitter layer depth